Recycled and mechanically activated concrete fines as a complete substitute for Portland cement − Feasibility and life cycle assessment - Magdalena Rajczakowska; Ankit Kothari; Thanyarat Buasiri; Andrzej Cwirzen (Case Studies in Construction Materials)
Construction and demolition waste (CDW) puts significant pressure on landfills and natural resources worldwide. Although partial substitutions of Portland cement (PC) with various recycled materials have been reported, a complete (100 %) replacement using recycled concrete remains problematic. In the present study, a novel binder was produced entirely from recycled concrete fines (RCF), while recycled aggregates were incorporated to replace virgin aggregates. High-energy grinding in a planetary ball mill was applied to the RCF fraction below 150 µm. Particle size reduction occurred after grinding, resulting in a decrease in d50 from 139 μm to 3.18 μm. The intensity of the X-ray diffraction (XRD) peaks corresponding to muscovite, microcline, and portlandite decreased significantly. On the other hand, quartz was only slightly affected. Activated RCF was used as a 100 % PC replacement in paste and concrete mixes. Compressive strengths of approximately 20 MPa were obtained after 28 days in laboratory tests for concrete with w/c equal to 0.6. A preliminary life cycle assessment (LCA) was performed to evaluate the environmental impacts, focusing on carbon emissions and resource depletion. The LCA results suggested over 90 % reduction in CO2 emissions compared to traditional cement-based mixes. Even at the laboratory-scale milling with high energy consumption per 1 kg of RCF, the impacts correspond to 50 % of traditional concrete (TC). Benefits remain significant over short transporting distances of the processed recycled ingredients; however, resource depletion exceeds TC after about 200 kilometers, and carbon emissions go beyond TC after approximately 800 kilometers.